Effect of thyroxine on munc-18 and syntaxin-1 expression in dorsal hippocampus of adult-onset hypothyroid rats - Zhu, Y. (PAGEPress Publications, 2012)
Adult-onset hypothyroidism induces a variety of impairments on hippocampus- dependent neurocognitive functioningin which many synaptic proteins in hippocampus neurons are involved. Here, we observed the effect of adult-onset hypothyroidism on the expression of syntaxin-1 and munc-18 in the dorsal hippocampus and whether the altered proteins could be restored by levothyroxine (T(4)) treatment. All rats were separated into 4 groups randomly: hypothyroid group, 5 µg T(4) /100 g body weight (BW) treated group, 20 µg T(4)/100 g BW treated group and control group. The radioimmunoassay kits were applied to assay the levels of serum T(3) and T(4), and the levels of syntaxin-1 and munc-18 in hippocampus were assessed by immunohistochemistry and Western blot. Both analysis corroborated that syntaxin-1 in the hypothyroid group was significantly higher. Munc-18 was lower in four layers of CA3 and dentate gyrus by immunohistochemistry. After two weeks of treatment with 5 µg T(4)/100 g BW for hypothyroidism, syntaxin-1 levels were completely restored, whereas the recovery of munc-18 only located in two of the four impaired layers. Twenty µg T(4)/100 g BW treatment normalized munc-18 levels. These data suggested that adult-onset hypothyroidism induced increment of syntaxin-1 and decrement of munc-18 in the dorsal hippocampus, which could be restored by T(4) treatment. Larger dosage of T(4) caused more effective restorations.